High-strength and high-ductility low-carbon alkali-activated cementing material and preparation method thereof
By modifying the synergistic effect of nano silicon carbide fibers and polyethylene fibers, combining alkali-excited industrial blast furnace waste slag and high-aluminum silicon powder, forming a three-dimensional network structure, solving the problem of insufficient ductility and strength of existing alkali-excited gelling materials. , realizes the preparation of high-strength, high-ductility, low-carbon alkali excitation gelling materials, and meets the national standard mechanical strength standards.
Patent Information
- Application Number
- CN202411370585.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-10
AI Technical Summary
The existing alkali-exciting gelling materials have poor ductility and low strength, making it difficult to meet the requirements of high strength and high ductility.
Modified nano silicon carbide fibers and polyethylene fibers are used to stimulate industrial blast furnace waste slag and high alumina silicon powder through alkali to form a three-dimensional three-dimensional network structure with C-A-S-H and N-A-S-H, and the high tensile strength of nano silicon carbide fibers and High elastic modulus, combined with the bridge and torsion effect of polyethylene fibers, improves the strength and ductility of the material.
The preparation of high-strength, high-ductility, low-carbon alkali excitation gelling materials has been achieved. The compressive strength of 28d is above 60MPa and the flexural strength is above 7MPa. It meets the national standard mechanical strength standards, and obtains tensile strength of more than 5MPa and more than 5% The strain rate significantly improves the ductile behavior of the material.
Smart Images

Figure CN119285280A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a cementitious material, in particular to a high-strength, high-ductility, low-carbon alkali-activated cementitious material and a preparation method thereof. Background Art
[0002] Alkali-activated cementitious materials, also known as "chemically activated cementitious materials", are hydraulic cementitious materials made by the catalytic principle of alkali activators (caustic soda, alkali-containing silicates, aluminates). They include alkali-glossterm] slag cement, geopolymer or geopolymer cement, etc. They are mainly composed of natural minerals or industrial waste residues (such as metakaolin, slag, fly ash, silica fume, steel slag, etc.) calcined with aluminum silicates with a certain rapid cooling and thermal history and alkali activators. Alkali-activated cementitious materials utilize a large amount of industrial solid waste, solve the land pollution problem caused by the original long-term accumulation and disposal method, and greatly reduce the use of cement, thereby reducing carbon emissions and saving costs. However, the disadvantages of the existing alkali-activated cementitious materials are poor ductility and low strength, which are manifested as low tensile properties and cracks. The Chinese invention patent (CN 112919856A) discloses a fiber geopolymer concrete and a preparation method thereof, which combines polyacrylonitrile fiber with alkali activation technology to improve the mechanical strength of alkali-activated cementitious materials, but does not mention ductility enhancement. Patent No. (CN 115594453A) discloses a fiber geopolymer board and its preparation method, which effectively inhibits frosting and improves flexural strength, but does not mention compressive strength and ductile behavior. Chinese invention patent (CN 115286301A) discloses a multi-scale fiber-reinforced alkali-activated gelling material and its preparation method, combining nanofibers with micron fibers to improve ductile behavior, but does not involve mechanical enhancement.
[0003] Therefore, it is necessary to provide a new method to meet the strength standards while improving the ductility of low-carbon alkali-activated cementitious materials and preparation methods. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a high-strength, high-ductility low-carbon alkali-activated cementitious material and a preparation method thereof, which has the characteristics of high strength, high ductility, simple preparation process, etc.
[0005] The high-strength, high-ductility, low-carbon alkali-activated gelling material of the present invention comprises a raw material of modified nano silicon carbide fiber and polyethylene fiber, wherein the modified nano silicon carbide fiber is formed by acid-modified nano silicon carbide fiber to form silanol groups on the surface converted from amorphous oxides;
[0006] Further, the nano silicon carbide fiber is placed in a hydrochloric acid solution, immersed at a temperature of 40° C. for 24 hours, and then washed and dried to obtain a modified nano silicon carbide fiber;
[0007] Furthermore, the raw materials of the gelling material include the following components by mass: 50-60 parts of industrial blast furnace slag, 8-12 parts of aluminum-rich silicon powder, 6.8-10.2 parts of alkali activator, 0.55-0.75 parts of polyethylene fiber, 0.10-0.35 parts of modified nano silicon carbide fiber, and 13-16 parts of water;
[0008] Furthermore, the alkaline activator comprises water glass and sodium hydroxide, in parts by weight, 6-9 parts of water glass and 0.8-1.2 parts of sodium hydroxide;
[0009] Furthermore, the raw materials of the gelling material include the following components by mass: 55 parts of industrial blast furnace slag, 10 parts of aluminum-rich silicon powder, 7 parts of water glass, 1 part of sodium hydroxide, 0.65 parts of polyethylene fiber, 0.2 parts of modified nano silicon carbide fiber, and 14 parts of water;
[0010] Furthermore, the polyethylene fibers have an average length of 12 mm, an average diameter of 20 μm, and a density of 0.96 g / cm 3 ;
[0011] Furthermore, the aluminum-rich silicon powder includes SiO2 and Al2O3.
[0012] The present invention discloses a method for preparing a high-strength, high-ductility, low-carbon alkali-activated cementitious material, comprising the following steps:
[0013] S1, mixing industrial blast furnace slag and aluminum-rich silicon powder, and then adding polyethylene fiber to prepare a fiber-dry powder mixture;
[0014] S2, mixing the modified nano silicon carbide fiber and the alkaline activator, stirring them by magnetic force and ultrasonic force, and then adding water and the fiber-dry powder mixture and mixing them to obtain a fiber-dry powder mixture.
[0015] The beneficial effects of the present invention are as follows: a high-strength, high-ductility, low-carbon alkali-activated gelling material and a preparation method thereof of the present invention combine modified nano silicon carbide fibers with polyethylene fibers, and form a high-strength, high-ductility, low-carbon alkali-activated gelling material by alkali-activated industrial blast furnace waste slag and high-aluminum silicon powder. Under strong acid conditions, the original nano silicon carbide fibers form silanol groups converted from amorphous oxides on the surface, which effectively improve the dispersibility and exert a synergistic effect with polyethylene fibers to achieve meso-microscopic ductility and strength modification. Under alkali activation, industrial solid waste blast furnace slag and high-aluminum silicon powder form a three-dimensional network structure with CASH and NASH combined. Due to the inherent high tensile strength and high elastic modulus of nano silicon carbide fibers, nano silicon carbide fibers are introduced to achieve bridging and filling, crack deflection and embedding effects of low-carbon alkali-activated gelling materials at the nanoscale, thereby achieving ductility and strength enhancement; at the same time, polyethylene fibers, as micrometer-scale materials, achieve bridging, torsion and pull-out effects, thereby improving ductility and strength at the mesoscale. The high-strength, high-ductility, low-carbon alkali-activated cementitious material of the present invention not only turns waste into treasure, but also has a simple preparation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The present invention will be further described below in conjunction with the accompanying drawings and embodiments:
[0017] Figure 1 The polyethylene fiber in the structure of the high-strength, high-ductility low-carbon alkali-activated gelling material prepared in Example 5
[0018] SEM images of the effect;
[0019] Figure 2 Preparation of modified nano silicon carbide fibers in high-strength, high-ductility low-carbon alkali-activated cementitious materials for Example 5
[0020] SEM image of the effect in the structure. DETAILED DESCRIPTION
[0021] The high-strength, high-ductility low-carbon alkali-activated cementitious material of this embodiment, the raw materials of the cementitious material include modified nano silicon carbide fibers and polyethylene fibers, the modified nano silicon carbide fibers are formed by acid-modified nano silicon carbide fibers to form silanol groups converted from amorphous oxides on the surface; the original nano silicon carbide fibers form silanol groups converted from amorphous oxides on the surface under strong acid conditions, which effectively improves the dispersibility and exerts a synergistic effect with the polyethylene fibers. Due to the inherent high tensile strength and high elastic modulus of nano silicon carbide fibers, the introduction of nano silicon carbide fibers realizes the bridging and filling, crack deflection and embedding effects of low-carbon alkali-activated cementitious materials at the nanoscale, and realizes ductility and strength enhancement; at the same time, polyethylene fibers as micrometer-scale materials realize bridging, torsion and pull-out effects, and improve ductility and strength from a mesoscopic perspective.
[0022] In this embodiment, the nano silicon carbide fiber is placed in a hydrochloric acid solution, soaked at a temperature of 40°C for 24 hours, and then washed and dried to obtain a modified nano silicon carbide fiber; water glass and sodium hydroxide are mixed and stirred by weight and cooled to room temperature to obtain an alkaline activator solution; the original nano silicon carbide fiber is placed in a 0.1M hydrochloric acid solution by weight, soaked at 40°C for 24 hours, and then washed and dried with ultrapure water to obtain a modified nano silicon carbide fiber. In this case, the amorphous oxide attached to the surface of the silicon carbide nanofiber is removed, and silanol groups are generated on the surface.
[0023] In this embodiment, the raw materials of the cementitious material include the following components by weight: 50-60 parts of industrial blast furnace slag, 8-12 parts of aluminum-rich silicon powder, 6.8-10.2 parts of alkali activator, 0.55-0.75 parts of polyethylene fiber, 0.10-0.35 parts of modified nano silicon carbide fiber, and 13-16 parts of water; the alkali activator includes water glass and sodium hydroxide, by weight, 6-9 parts of water glass and 0.8-1.2 parts of sodium hydroxide. Under alkali excitation, industrial solid waste blast furnace slag and high aluminum silicon powder form a three-dimensional network structure with CASH and NASH combined. At the same time, due to the inherent high tensile strength and high elastic modulus of nano silicon carbide fibers, nano silicon carbide fibers are introduced to realize the bridging and filling, crack deflection and embedding effects of low carbon alkali-activated cementitious materials at the nanoscale, and realize ductility and strength enhancement; at the same time, polyethylene fibers as micrometer-scale materials realize bridging, torsion and pull-out effects, and improve ductility and strength from the mesoscopic perspective. The slag comprises the following components by mass: SiO2 36.40wt%; Al2O3 17.80wt%; CaO 35.80wt%; Fe2O3 1.23wt%; MgO 5.91wt%; K2O 0.10wt%; Na2O 0.38wt%; SO3 0.10wt%; TiO2 0.10wt%; and other 2.20wt%. The aluminum-rich silicon powder comprises the following components by mass: SiO2 53.32wt%; Al2O3 45.17wt%; and other 1.51wt%.
[0024] In a preferred embodiment, the raw materials of the cementitious material include the following components by mass: 55 parts of industrial blast furnace slag, 10 parts of aluminum-rich silicon powder, 7 parts of water glass, 1 part of sodium hydroxide, 0.65 parts of polyethylene fiber, 0.2 parts of modified nano silicon carbide fiber, and 14 parts of water; the average length of the polyethylene fiber is 12 mm, the average diameter is 20 μm, and the density is 0.96 g / cm 3 .
[0025] This embodiment also discloses a method for preparing a high-strength, high-ductility, low-carbon alkali-activated cementitious material, comprising the following steps:
[0026] S1, industrial blast furnace slag and aluminum-rich silicon powder are stirred and mixed, and then polyethylene fiber is added to obtain a fiber-dry powder mixture: industrial blast furnace slag and aluminum-rich silicon powder are stirred at 70-80r / min for 1-2 minutes at room temperature to obtain a dry powder mixture; polyethylene fiber is slowly added to the dry powder mixture stirred at 70-80r / min and stirred again for 1-2 minutes to obtain a fiber-dry powder mixture
[0027] S2, the modified nano silicon carbide fiber and the alkaline activator are mixed and subjected to magnetic stirring and ultrasonic stirring, and then water and the fiber-dry powder mixture are added and mixed to obtain a fiber-dry powder mixture: the modified nano silicon carbide fiber is added to the alkaline activator solution according to mass, and magnetic stirring is performed at 1000r / min for 20min and ultrasonic stirring is performed at 80% amplitude for 5min to obtain an alkaline activator mixed solution; the alkaline activator mixed solution and water are added to the fiber-dry powder mixture according to mass, and stirred at 150-160r / min for 1-2min to obtain a high-strength, high-ductility low-carbon alkali-activated cementitious material.
[0028] Embodiment 1
[0029] The present embodiment provides a high-strength, high-ductility, low-carbon alkali-activated cementitious material, wherein the raw materials include, by mass, 55 parts of industrial blast furnace slag, 10 parts of aluminum-rich silicon powder, 7 parts of water glass, 0.9 parts of sodium hydroxide, 0.55 parts of polyethylene fiber, 0.10 parts of modified nano silicon carbide fiber, and 14 parts of water.
[0030] A method for preparing a high-strength, high-ductility low-carbon alkali-activated cementitious material according to this embodiment comprises the following steps:
[0031] S1: 55 parts of industrial blast furnace slag and 12 parts of aluminum-rich silicon powder are stirred at 70-80r / min for 1-2 minutes at room temperature to obtain a dry powder mixture; 0.55 parts of polyethylene fiber are slowly added to the dry powder mixture stirred at 70-80r / min and stirred again for 1-2 minutes to obtain a fiber-dry powder mixture;
[0032] S2: Mix 7 parts of water glass and 0.9 parts of sodium hydroxide, stir and cool to room temperature to obtain an alkaline activator solution; put the original nano-silicon carbide fiber into a 0.1M hydrochloric acid solution, soak it at 40°C for 24 hours, then wash and dry it with ultrapure water to obtain 0.10 parts of modified nano-silicon carbide fiber.
[0033] S3: adding 0.10 parts of modified nano silicon carbide fiber to the alkaline activator solution, and performing magnetic stirring at 1000 r / min for 20 min and ultrasonic stirring at 80% amplitude for 5 min to obtain an alkaline activator mixed solution;
[0034] S4: Add the alkali activator mixed solution and water into the fiber-dry powder mixture according to the mass parts and stir at 150-160r / min for 1-2min to obtain a high-strength, high-ductility, low-carbon alkali-activated cementitious material.
[0035] Embodiment 2
[0036] The present embodiment provides a high-strength, high-ductility, low-carbon alkali-activated cementitious material, wherein the raw materials include, by mass, 55 parts of industrial blast furnace slag, 10 parts of aluminum-rich silicon powder, 7.5 parts of water glass, 1.0 part of sodium hydroxide, 0.60 part of polyethylene fiber, 0.10 part of modified nano silicon carbide fiber, and 15 parts of water.
[0037] A method for preparing a high-strength, high-ductility low-carbon alkali-activated cementitious material according to this embodiment comprises the following steps:
[0038] S1: 55 parts of industrial blast furnace slag and 10 parts of aluminum-rich silicon powder are stirred at 70-80 r / min for 1-2 minutes at room temperature to obtain a dry powder mixture; 0.60 parts of polyethylene fiber are slowly added to the dry powder mixture stirred at 70-80 r / min and stirred again for 1-2 minutes to obtain a fiber-dry powder mixture;
[0039] S2: Mix 7.5 parts of water glass and 1.0 part of sodium hydroxide, stir and cool to room temperature to obtain an alkaline activator solution; put the original nano-silicon carbide fiber into a 0.1M hydrochloric acid solution, soak it at 40°C for 24 hours, then wash and dry it with ultrapure water to obtain 0.10 parts of modified nano-silicon carbide fiber.
[0040] S3: adding 0.10 parts of modified nano silicon carbide fiber to the alkaline activator solution, and performing magnetic stirring at 1000 r / min for 20 min and ultrasonic stirring at 80% amplitude for 5 min to obtain an alkaline activator mixed solution;
[0041] S4: Add the alkali activator mixed solution and water into the fiber-dry powder mixture according to the mass parts and stir at 150-160r / min for 1-2min to obtain a high-strength, high-ductility, low-carbon alkali-activated cementitious material.
[0042] Embodiment 3
[0043] The present embodiment provides a high-strength, high-ductility, low-carbon alkali-activated cementitious material, wherein the raw materials include, by mass, 55 parts of industrial blast furnace slag, 11 parts of aluminum-rich silicon powder, 7 parts of water glass, 0.9 parts of sodium hydroxide, 0.75 parts of polyethylene fiber, 0.10 parts of modified nano silicon carbide fiber, and 14 parts of water.
[0044] A method for preparing a high-strength, high-ductility low-carbon alkali-activated cementitious material according to this embodiment comprises the following steps:
[0045] S1: 55 parts of industrial blast furnace slag and 11 parts of aluminum-rich silicon powder are stirred at room temperature at 70-80r / min for 1-2 minutes to obtain a dry powder mixture; 0.75 parts of polyethylene fiber are slowly added to the dry powder mixture stirred at 70-80r / min and stirred again for 1-2 minutes to obtain a fiber-dry powder mixture;
[0046] S2: Mix 7 parts of water glass and 0.9 parts of sodium hydroxide, stir and cool to room temperature to obtain an alkaline activator solution; put the original nano-silicon carbide fiber into a 0.1M hydrochloric acid solution, soak it at 40°C for 24 hours, then wash and dry it with ultrapure water to obtain 0.10 parts of modified nano-silicon carbide fiber.
[0047] S3: adding 0.10 parts of modified nano silicon carbide fiber to the alkaline activator solution, and performing magnetic stirring at 1000 r / min for 20 min and ultrasonic stirring at 80% amplitude for 5 min to obtain an alkaline activator mixed solution;
[0048] S4: Add the alkali activator mixed solution and water into the fiber-dry powder mixture according to the mass parts and stir at 150-160r / min for 1-2min to obtain a high-strength, high-ductility, low-carbon alkali-activated cementitious material.
[0049] Embodiment 4
[0050] The present embodiment provides a high-strength, high-ductility, low-carbon alkali-activated cementitious material, wherein the raw materials include, by mass, 55 parts of industrial blast furnace slag, 11 parts of aluminum-rich silicon powder, 7 parts of water glass, 1.0 part of sodium hydroxide, 0.55 parts of polyethylene fiber, 0.25 parts of modified nano silicon carbide fiber, and 16 parts of water.
[0051] A method for preparing a high-strength, high-ductility low-carbon alkali-activated cementitious material according to this embodiment comprises the following steps:
[0052] S1: 55 parts of industrial blast furnace slag and 11 parts of aluminum-rich silicon powder are stirred at 70-80 r / min for 1-2 minutes at room temperature to obtain a dry powder mixture; 0.55 parts of polyethylene fiber are slowly added to the dry powder mixture stirred at 70-80 r / min and stirred again for 1-2 minutes to obtain a fiber-dry powder mixture;
[0053] S2: Mix 7 parts of water glass and 1.0 part of sodium hydroxide, stir and cool to room temperature to obtain an alkaline activator solution; put the original nano-silicon carbide fiber into a 0.1M hydrochloric acid solution, soak it at 40°C for 24 hours, then wash and dry it with ultrapure water to obtain 0.25 parts of modified nano-silicon carbide fiber.
[0054] S3: adding 0.25 parts of modified nano silicon carbide fiber to the alkaline activator solution, and performing magnetic stirring at 1000 r / min for 20 min and ultrasonic stirring at 80% amplitude for 5 min to obtain an alkaline activator mixed solution;
[0055] S4: Add the alkali activator mixed solution and water into the fiber-dry powder mixture according to the mass parts and stir at 150-160r / min for 1-2min to obtain a high-strength, high-ductility, low-carbon alkali-activated cementitious material.
[0056] Embodiment 5
[0057] The present embodiment provides a high-strength, high-ductility, low-carbon alkali-activated cementitious material, wherein the raw materials include, by mass, 55 parts of industrial blast furnace slag, 10 parts of aluminum-rich silicon powder, 7.5 parts of water glass, 1.1 parts of sodium hydroxide, 0.60 parts of polyethylene fiber, 0.25 parts of modified nano silicon carbide fiber, and 14 parts of water.
[0058] A method for preparing a high-strength, high-ductility low-carbon alkali-activated cementitious material according to this embodiment comprises the following steps:
[0059] S1: 55 parts of industrial blast furnace slag and 10 parts of aluminum-rich silicon powder are stirred at 70-80 r / min for 1-2 minutes at room temperature to obtain a dry powder mixture; 0.60 parts of polyethylene fiber are slowly added to the dry powder mixture stirred at 70-80 r / min and stirred again for 1-2 minutes to obtain a fiber-dry powder mixture;
[0060] S2: Mix 7.5 parts of water glass and 1.1 parts of sodium hydroxide, stir and cool to room temperature to obtain an alkaline activator solution; put the original nano-silicon carbide fiber into a 0.1M hydrochloric acid solution, soak it at 40°C for 24 hours, then wash and dry it with ultrapure water to obtain 0.25 parts of modified nano-silicon carbide fiber.
[0061] S3: adding 0.25 parts of modified nano silicon carbide fiber to the alkaline activator solution, and performing magnetic stirring at 1000 r / min for 20 min and ultrasonic stirring at 80% amplitude for 5 min to obtain an alkaline activator mixed solution;
[0062] S4: Add the alkali activator mixed solution and water into the fiber-dry powder mixture according to the mass parts and stir at 150-160r / min for 1-2min to obtain a high-strength, high-ductility, low-carbon alkali-activated cementitious material.
[0063] Embodiment 6
[0064] The present embodiment provides a high-strength, high-ductility, low-carbon alkali-activated cementitious material, wherein the raw materials include, by mass, 55 parts of industrial blast furnace slag, 11 parts of aluminum-rich silicon powder, 7.0 parts of water glass, 1.0 part of sodium hydroxide, 0.75 part of polyethylene fiber, 0.25 part of modified nano silicon carbide fiber, and 15 parts of water.
[0065] A method for preparing a high-strength, high-ductility low-carbon alkali-activated cementitious material according to this embodiment comprises the following steps:
[0066] S1: 55 parts of industrial blast furnace slag and 11 parts of aluminum-rich silicon powder are stirred at room temperature at 70-80r / min for 1-2 minutes to obtain a dry powder mixture; 0.75 parts of polyethylene fiber are slowly added to the dry powder mixture stirred at 70-80r / min and stirred again for 1-2 minutes to obtain a fiber-dry powder mixture;
[0067] S2: Mix 7.0 parts of water glass and 1.0 part of sodium hydroxide, stir and cool to room temperature to obtain an alkaline activator solution; put the original nano-silicon carbide fiber into a 0.1M hydrochloric acid solution, soak it at 40°C for 24 hours, then wash and dry it with ultrapure water to obtain 0.25 parts of modified nano-silicon carbide fiber.
[0068] S3: adding 0.25 parts of modified nano silicon carbide fiber to the alkaline activator solution, and performing magnetic stirring at 1000 r / min for 20 min and ultrasonic stirring at 80% amplitude for 5 min to obtain an alkaline activator mixed solution;
[0069] S4: Add the alkali activator mixed solution and water into the fiber-dry powder mixture according to the mass parts and stir at 150-160r / min for 1-2min to obtain a high-strength, high-ductility, low-carbon alkali-activated cementitious material.
[0070] Embodiment 7
[0071] The present embodiment provides a high-strength, high-ductility, low-carbon alkali-activated cementitious material, wherein the raw materials include, by mass, 55 parts of industrial blast furnace slag, 12 parts of aluminum-rich silicon powder, 7.0 parts of water glass, 1.2 parts of sodium hydroxide, 0.55 parts of polyethylene fiber, 0.35 parts of modified nano silicon carbide fiber, and 16 parts of water.
[0072] A method for preparing a high-strength, high-ductility low-carbon alkali-activated cementitious material according to this embodiment comprises the following steps:
[0073] S1: 55 parts of industrial blast furnace slag and 12 parts of aluminum-rich silicon powder are stirred at 70-80r / min for 1-2 minutes at room temperature to obtain a dry powder mixture; 0.55 parts of polyethylene fiber are slowly added to the dry powder mixture stirred at 70-80r / min and stirred again for 1-2 minutes to obtain a fiber-dry powder mixture;
[0074] S2: Mix 7.0 parts of water glass and 1.2 parts of sodium hydroxide, stir and cool to room temperature to obtain an alkaline activator solution; put the original nano-silicon carbide fiber into a 0.1M hydrochloric acid solution, soak it at 40°C for 24 hours, then wash and dry it with ultrapure water to obtain 0.35 parts of modified nano-silicon carbide fiber.
[0075] S3: adding 0.35 parts of modified nano silicon carbide fiber to the alkaline activator solution, and performing magnetic stirring at 1000 r / min for 20 min and ultrasonic stirring at 80% amplitude for 5 min to obtain an alkaline activator mixed solution;
[0076] S4: Add the alkali activator mixed solution and water into the fiber-dry powder mixture according to the mass parts and stir at 150-160r / min for 1-2min to obtain a high-strength, high-ductility, low-carbon alkali-activated cementitious material.
[0077] Embodiment 8
[0078] The present embodiment provides a high-strength, high-ductility, low-carbon alkali-activated cementitious material, wherein the raw materials include, by mass, 55 parts of industrial blast furnace slag, 11 parts of aluminum-rich silicon powder, 7.5 parts of water glass, 1.0 part of sodium hydroxide, 0.60 part of polyethylene fiber, 0.35 part of modified nano silicon carbide fiber, and 14 parts of water.
[0079] A method for preparing a high-strength, high-ductility low-carbon alkali-activated cementitious material according to this embodiment comprises the following steps:
[0080] S1: 55 parts of industrial blast furnace slag and 11 parts of aluminum-rich silicon powder are stirred at 70-80r / min for 1-2 minutes at room temperature to obtain a dry powder mixture; 0.60 parts of polyethylene fiber are slowly added to the dry powder mixture stirred at 70-80r / min and stirred again for 1-2 minutes to obtain a fiber-dry powder mixture;
[0081] S2: Mix 7.5 parts of water glass and 1.0 part of sodium hydroxide, stir and cool to room temperature to obtain an alkaline activator solution; put the original nano-silicon carbide fiber into a 0.1M hydrochloric acid solution, soak it at 40°C for 24 hours, then wash and dry it with ultrapure water to obtain 0.35 parts of modified nano-silicon carbide fiber.
[0082] S3: adding 0.35 parts of modified nano silicon carbide fiber to the alkaline activator solution, and performing magnetic stirring at 1000 r / min for 20 min and ultrasonic stirring at 80% amplitude for 5 min to obtain an alkaline activator mixed solution;
[0083] S4: Add the alkali activator mixed solution and water into the fiber-dry powder mixture according to the mass parts and stir at 150-160r / min for 1-2min to obtain a high-strength, high-ductility, low-carbon alkali-activated cementitious material.
[0084] Embodiment 9
[0085] The present embodiment provides a high-strength, high-ductility, low-carbon alkali-activated cementitious material, wherein the raw materials include, by mass, 55 parts of industrial blast furnace slag, 11 parts of aluminum-rich silicon powder, 7.0 parts of water glass, 1.2 parts of sodium hydroxide, 0.75 parts of polyethylene fiber, 0.35 parts of modified nano silicon carbide fiber, and 15 parts of water.
[0086] A method for preparing a high-strength, high-ductility low-carbon alkali-activated cementitious material according to this embodiment comprises the following steps:
[0087] S1: 55 parts of industrial blast furnace slag and 11 parts of aluminum-rich silicon powder are stirred at room temperature at 70-80r / min for 1-2 minutes to obtain a dry powder mixture; 0.75 parts of polyethylene fiber are slowly added to the dry powder mixture stirred at 70-80r / min and stirred again for 1-2 minutes to obtain a fiber-dry powder mixture;
[0088] S2: Mix 7.0 parts of water glass and 1.2 parts of sodium hydroxide, stir and cool to room temperature to obtain an alkaline activator solution; put the original nano-silicon carbide fiber into a 0.1M hydrochloric acid solution, soak it at 40°C for 24 hours, then wash and dry it with ultrapure water to obtain 0.35 parts of modified nano-silicon carbide fiber.
[0089] S3: adding 0.35 parts of modified nano silicon carbide fiber to the alkaline activator solution, and performing magnetic stirring at 1000 r / min for 20 min and ultrasonic stirring at 80% amplitude for 5 min to obtain an alkaline activator mixed solution;
[0090] S4: Add the alkali activator mixed solution and water into the fiber-dry powder mixture according to the mass parts and stir at 150-160r / min for 1-2min to obtain a high-strength, high-ductility, low-carbon alkali-activated cementitious material.
[0091] Comparative Example 1
[0092] The comparative example is a high-strength, high-ductility low-carbon alkali-activated cementitious material, the raw materials of which include, by mass, 55 parts of industrial blast furnace slag, 11 parts of aluminum-rich silicon powder, 7.0 parts of water glass, 1.2 parts of sodium hydroxide, 0.55 parts of polyethylene fiber, and 15 parts of water.
[0093] A method for preparing a high-strength, high-ductility low-carbon alkali-activated cementitious material according to this embodiment comprises the following steps:
[0094] S1: 55 parts of industrial blast furnace slag and 11 parts of aluminum-rich silicon powder are stirred at 70-80 r / min for 1-2 minutes at room temperature to obtain a dry powder mixture; 0.55 parts of polyethylene fiber are slowly added to the dry powder mixture stirred at 70-80 r / min and stirred again for 1-2 minutes to obtain a fiber-dry powder mixture;
[0095] S2: 7.0 parts of water glass and 1.2 parts of sodium hydroxide were mixed and stirred and cooled to room temperature to obtain an alkaline activator solution;
[0096] S3: Add alkali activator solution and water according to mass parts into the fiber-dry powder mixture and stir at 150-160r / min for 1-2min to obtain a high-strength, high-ductility, low-carbon alkali-activated cementitious material.
[0097] Comparative Example 2
[0098] The comparative example is a high-strength, high-ductility low-carbon alkali-activated cementitious material, the raw materials of which include, by mass, 55 parts of industrial blast furnace slag, 11 parts of aluminum-rich silicon powder, 7.0 parts of water glass, 1.1 parts of sodium hydroxide, 0.60 parts of polyethylene fiber, and 14 parts of water.
[0099] A method for preparing a high-strength, high-ductility low-carbon alkali-activated cementitious material according to this embodiment comprises the following steps:
[0100] S1: 55 parts of industrial blast furnace slag and 11 parts of aluminum-rich silicon powder are stirred at 70-80r / min for 1-2 minutes at room temperature to obtain a dry powder mixture; 0.60 parts of polyethylene fiber are slowly added to the dry powder mixture stirred at 70-80r / min and stirred again for 1-2 minutes to obtain a fiber-dry powder mixture;
[0101] S2: 7.0 parts of water glass and 1.1 parts of sodium hydroxide were mixed and stirred and cooled to room temperature to obtain an alkaline activator solution;
[0102] S3: Add alkali activator solution and water according to mass parts into the fiber-dry powder mixture and stir at 150-160r / min for 1-2min to obtain a high-strength, high-ductility, low-carbon alkali-activated cementitious material.
[0103] Comparative Example 3
[0104] The comparative example is a high-strength, high-ductility low-carbon alkali-activated cementitious material, the raw materials of which include, by mass, 55 parts of industrial blast furnace slag, 12 parts of aluminum-rich silicon powder, 7.0 parts of water glass, 1.1 parts of sodium hydroxide, 0.75 parts of polyethylene fiber, and 16 parts of water.
[0105] A method for preparing a high-strength, high-ductility low-carbon alkali-activated cementitious material according to this embodiment comprises the following steps:
[0106] S1: 55 parts of industrial blast furnace slag and 12 parts of aluminum-rich silicon powder are stirred at 70-80r / min for 1-2 minutes at room temperature to obtain a dry powder mixture; 0.75 parts of polyethylene fiber are slowly added to the dry powder mixture stirred at 70-80r / min and stirred again for 1-2 minutes to obtain a fiber-dry powder mixture;
[0107] S2: 7.0 parts of water glass and 1.1 parts of sodium hydroxide were mixed and stirred and cooled to room temperature to obtain an alkaline activator solution;
[0108] S3: Add alkali activator solution and water according to mass parts into the fiber-dry powder mixture and stir at 150-160r / min for 1-2min to obtain a high-strength, high-ductility, low-carbon alkali-activated cementitious material.
[0109] The compressive strength, flexural strength, tensile strength and strain rate results of each embodiment and each comparative example 28d are shown in Table 1.
[0110]
[0111] Combined with the data in Table 1 above, it can be seen that the present invention has prepared a 28d compressive strength of more than 60MPa and a 28d flexural strength of more than 7MPa, which meets the national standard for mechanical strength. At the same time, a tensile strength of more than 5MPa and a strain rate of more than 5% are obtained, which significantly improves the ductile behavior. This is related to the synergistic effect of polyethylene fiber and modified nano silicon carbide fiber. Industrial blast furnace waste slag is combined with high-aluminum silicon powder and alkali activator to prepare a microstructure with a three-dimensional network, and C(N)-ASH gelling is obtained. From a microscopic point of view, the modified nano silicon carbide fiber plays a nano-filling effect and a bridging effect, effectively connecting microcracks and micropores. At the same time, the high toughness of the appropriate amount of nanofibers themselves improves the mechanical strength of the low-carbon alkali-activated gelling material, refer to the above examples and comparative examples; from a mesoscopic point of view, polyethylene fibers bridge the fracture effect caused by external stress. The synergistic effect of the two enables the low-carbon alkali-activated gelling material to obtain high strength and high ductility properties.
[0112] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A high-strength, high-ductility, low-carbon alkali-activated cementitious material, characterized by: The raw materials of the gelling material include modified nano silicon carbide fibers and polyethylene fibers. The modified nano silicon carbide fibers are prepared by acid-modified nano silicon carbide fibers to form silanol groups on the surface of the fibers which are converted from amorphous oxides.
2. The high-strength, high-ductility, low-carbon alkali-activated cementitious material according to claim 1, characterized in that: The nano silicon carbide fiber is placed in a hydrochloric acid solution, immersed at a temperature of 40° C. for 24 hours, and then washed and dried to obtain a modified nano silicon carbide fiber.
3. The high-strength, high-ductility, low-carbon alkali-activated cementitious material according to claim 1, characterized in that: The raw materials of the gelling material include the following components by mass: 50-60 parts of industrial blast furnace slag, 8-12 parts of aluminum-rich silicon powder, 6.8-10.2 parts of alkali activator, 0.55-0.75 parts of polyethylene fiber, 0.10-0.35 parts of modified nano silicon carbide fiber, and 13-16 parts of water.
4. The high-strength, high-ductility, low-carbon alkali-activated cementitious material according to claim 3, characterized in that: The alkaline activator comprises water glass and sodium hydroxide, wherein the water glass comprises 6-9 parts and the sodium hydroxide comprises 0.8-1.2 parts by weight.
5. The high-strength, high-ductility, low-carbon alkali-activated cementitious material according to claim 4, characterized in that: The raw materials of the cementitious material include the following components by mass: 55 parts of industrial blast furnace slag, 10 parts of aluminum-rich silicon powder, 7 parts of water glass, 1 part of sodium hydroxide, 0.65 parts of polyethylene fiber, 0.2 parts of modified nano silicon carbide fiber, and 14 parts of water.
6. The high-strength, high-ductility, low-carbon alkali-activated cementitious material according to claim 3, characterized in that: The polyethylene fibers have an average length of 12 mm, an average diameter of 20 μm, and a density of 0.96 g / cm 3 .
7. The high-strength, high-ductility, low-carbon alkali-activated cementitious material according to claim 3, characterized in that: The aluminum-rich silicon powder includes SiO2 and Al2O3.
8. A method for preparing a high-strength, high-ductility, low-carbon alkali-activated cementitious material, characterized in that: The following steps are involved: S1, mixing industrial blast furnace slag and aluminum-rich silicon powder, and then adding polyethylene fiber to prepare a fiber-dry powder mixture; S2, mixing the modified nano silicon carbide fiber and the alkaline activator, stirring them by magnetic force and ultrasonic force, and then adding water and the fiber-dry powder mixture and mixing them to obtain a fiber-dry powder mixture.
Citation Information
Patent Citations
Fiber geopolymer concrete and preparation method thereof
CN112919856A
Multi-scale fiber-reinforced alkali-activated cementing material and preparation method thereof
CN115286301A
Fiber geopolymer plate and preparation method thereof
CN115594453A
Cited By
Matrix self-loading photocatalysis high-strength and high-toughness geopolymer and preparation method thereof
CN122254821A